Vijftig jaar kunstprijzen van de provincie West-Vlaanderen. (Brugge : Provinciale Dienst voor Cultuur, 1977)
Creytens, Jules ; Rotsaert, Octaaf ; Lateur, Karel ; Vandevoorde, Geo ; de Woude, Firmin Van ; Koentges, Firmin ; Allaert, M. ; Vansassenbroeck, Achiel ; Michiels, Geo ; Vandersmissen, Leo ; De Craeke, Gaston ; Poppe, Albert ; Dooms, Leopold ; Termote, Edgard ; Mannes, Henri ; Rommelaere, Dora ; Noreilde ; Poppe, Michel ; Vandersmissen, Frans ; Vandenberghe, René ; Swimberghe, Gilbert ; Aerts, Ernest ; Boel, Maurits ; De Sloovere, Odrada ; Permeke, Paul ; Setola, Albert ; Van Paemel, Leo ; Bonduel, Roger ; De Gheus, Lucien ; Bollion, Michel ; Vonck, Fernand (Ferdinand) ; Deck, Paul ; Deman, Julien ; Smis, Sylvain ; Burrick, Eric ; Dousselaere, Maurits ; Lannoy, Marie-Rose ; Taeckens, André ; Van Rafelghem, Paul ; Noreille, Joz ; Vonck, Fernand (Ferdinand) ; sohier, Fernand ; Dugardijn, Luc ; Petre, Jacques ; Decock, Fernand ; De Maeyer, Jacky ; Deneckere, Willem ; Van Houtryve-Mary, Albert ; Patoor, Pol ; Wittevrongel, Roger ; Depuydt, Steven ; Vandroemme, Adhemar ; Degroote-Tanghe, Georgette ; Spilliaert, Pol ; Van Dorpe-Huybrechts, Marie-Christine ; Desauvage, Marc ; Tanghe, Jan ; Missine, Bernard ; Claeys, Yvan ; Scherpereel, Hendrik ; Meurisse, Roger ; Minnebo, Hubert ; Theys, Yvan ; Van Damme, Eddy ; Driesschaert, Herwig ; Degroote-Tanghe, Georgette ; Deneckere, Willem ; Allemeersch, Geert ; Frimout, Cyr ; Canestraro, Livia ; Bosschaert, Renaat ; Vandekerckhove, Johan ; Brackez, Marcel ; Sterckx, André ; Neuttens, Albert ; Labarque, Jean-Pierre ; Bonneux, Edouard ; Beuckels, Victor ; Deleu, Frans ; Ghesquière, André ; Houbaert, Godfried ; Van Biervliet, Hendrik ; Vanassche, Eugène ; Vermeersch, Charles ; Deneckere, Willem ; Vervisch, Godfried ; Lannoy, Marie-Rose ; Fryns, Jan ; Van Rafelghem, Paul ; Decroubele, Luc ; Dupont, Karel ; etc.
boek
Keywords: West-Vlaanderen